Neuromodulation for substance addiction in human subjects: A review. (December 2018) - Bari, Ausaf; DiCesare, Jasmine; Babayan, Diana; Runcie, Mariama; Sparks, Hiro; Wilson, Bayard
Highlights: Substance abuse and addiction are serious and costly socioeconomic problems. Neuromodulation therapies have shown significant promise for treating addiction. DBS and transcranial techniques have gathered considerable research interest of late. The NAc is the most well-studied target with respect to DBS for addiction. Apprehension regarding the invasiveness of DBS for addiction must be addressed. Abstract: Substance abuse is one of the most prevalent and costly health problems in the world today. Standard medical therapy is often not curative, and relapse is common. Research over the past several decades on the neural underpinnings of addiction has implicated a network of structures within the brain shown to be altered in patients with substance abuse. The field of neuromodulation aims to utilize this knowledge to treat dysfunctional circuits by targeting and modulating specific brain circuits. While invasive neuromodulation such as DBS and VNS have proven to be effective in treating movement disorders, OCD and epilepsy, there is increasing interest and data with regards to its potential application for the treatment of severe, intractable addiction. Several neuromodulatory techniques and brain targets are currently under investigation in patients with various substance abuse disorders. This review aims to summarize the current state of evidence for neurosurgical neuromodulation as a therapy for substance abuse and addiction, and to provide additional expert opinions as to the obstacles and future directions of this endeavor.